Measuring the success of specific health problem consultations in cats and dogs: a systematic review - Corah, Louise; Mossop, Liz; Cobb, Kate; Dean, Rachel (BMJ Publishing Group, 2018)
Consultations are complex interactions, are central to achieving optimal outcomes for all stakeholders, yet what constitutes a successful consultation has not been defined. The aim of this systematic review was to describe the scope of the literature available on specific health problem consultations and appraise their identified success measures. Searches of CAB Abstracts and MEDLINE were performed in May 2016 using species and consultation terms. Systematic sorting of the results allowed identification of consultation ‘success factors’ cited in peer-reviewed veterinary literature which were appraised using an appropriate critical appraisal tool (AXIS). Searches returned 11 330 results with a total of 17 publications meeting the inclusion criteria, of which four measured consultation success. Journal of the American Veterinary Medical Association was the most common journal of publication (9 of 17) and the majority of included papers had been published since 2010 (12 of 17). Success factors measured were compliance, client satisfaction and veterinary surgeon satisfaction, and publications primarily used communication analysis tools to measure success. The review highlights the paucity of peer-reviewed literature examining small animal, health problem veterinary consultations. The available evidence is of variable quality and provides weak evidence as to which factors contribute to a successful consultation.